Animal giants - Johson, Jinny (United Kingdom : Miles Kelly, 2010)
"Animal Giants," part of the "Wild Nature" series, explores 20 of the world's biggest animals. Discover fascinating details about their size and unique features. Colorful pictures bring these massive creatures to life on the page. It's a great way to learn about the giants of the animal kingdom.
"Animal Giants" is a book that shows you 20 really big animals. It has cool pictures and tells you simple things about each one. You'll learn about how big they are and where they live. It's a fun and easy way to see some of the biggest animals in the world!
Keywords: Giants Animal